Decentralization and good governance of French-speaking West African states : contribution to the study of the case of Côte d'Ivoire - (:unkn) unknown (My University, 2019)
Africa, because of its weakness, its failures at many levels, and all the difficulties it faces in meeting the global standards of democracy, has over the years become the ideal receptacle for all kinds of experimentation on the issue of development.And it was only from a public finance crisis, the most emblematic manifestation of which was that of public debt, which had already begun a decade earlier, that Africans referred to structural adjustment policies. Strongly encouraged by international organizations, these countries have adopted decentralization as an effective means of good governance.Despite its adaptation in the various constitutions, decentralization really began only about fifteen years ago in many African countries such as Côte d’Ivoire, Senegal and Cameroon. Decentralization thus appears to be one of the best means of modernizing the centralized state, promoting citizen participation and good governance. It could, together with good governance, shed light on how the incumbent authorities manage state’s resources.Seen as a means of economic growth and development, decentralization and good governance, according to the observations of recent years, do not seem to have the same effects in the developing countries, still tribal and especially very poor and plagued by many problems. This model of territorial organization has just become a condition for receiving international assistance.What are the causes of the failure of decentralization in West Africa, and what are the means these countries possess in order to succeed in changing the democratic ideals still locked in ancestral rites and Customs?
Keywords: African Research